Pengelolaan Transportasi Berwawasan Lingkungan Sebagai Dampak Perkembangan Perkotaan Tak Terkendali (Studi Kasus Kota Semarang) - Purwanto, Djoko; Ismiyati, Ismiyati (Department of Civil Engineering, Diponegoro University, 2014)
The increasing of urban population growth would affect to the increasing settlement growth which expanding uncontrollably toward the suburbs, this condition will influence transportation problem and 70 % air pollution comes from transportation sector (BAPEDAL in 2006). Semarang cities as case study deals with congestion problems in almost all road network; the most surprising thing is with the presence of mass transit services which is BRT, both BRT corridor I and corridor II, it still have a load factor of 27% (Ilham Hussein, 2012). This study aims to: manage environmentally sound public transportation based on the characteristics of people and city of Semarang. The result of study concluded that in order to manage environmentally sound transportation by creating an unified and integrated mass transit; which is by cutting the BRT routes that are less effective and too long, directed to feeder transport from the tip end of track to the end of beginning of peple mobility with a public transport like mini bus for a distance of > 500m and bike or walking track to feeder within 200 – 500m equipped with convenient bicycle and pedestrian infrastructures. Whereas, for the suburbs mobility to other suburbs it can use rail-based mass transportation (MRT).